Retrograde Headless Intramedullary Screw Fixation for Displaced Fifth Metacarpal Neck and Shaft Fractures: Short Term Results - Doarn, Michael C. (Hand (N Y), 2014)
BACKGROUND: This study aimed to evaluate the early clinical outcomes of retrograde headless intramedullary screw fixation for displaced fifth metacarpal neck and shaft fractures. METHODS: We retrospectively reviewed nine patients treated with retrograde intramedullary screw fixation of fifth metacarpal neck and shaft fractures between 2011 and 2013. Patient demographics and outcomes including hand dominance, age, sex, type of injury, injury and postoperative radiographs, return to work, time to fracture union radiographically, complications, visual analog score, disabilities of the arm, shoulder, and hand scores, postoperative metacarpophalangeal joint range of motion, and grip strength were recorded. RESULTS: Nine fractures in nine patients with a mean age of 32 years (19–54) were included. There were seven metacarpal neck and two metacarpal shaft fractures. All patients sustained injury by direct impact of fist against an object. No case involved worker’s compensation. Patients had a mean follow-up of 36 weeks (6–57 weeks) and at the time of latest follow-up had no pain. Mean radiographic healing was 49 days (28–85 days). Mean return to work was 6 weeks (4–10 weeks). Mean metacarpalphalangeal joint motion was 0° extension and 90° flexion. Mean disabilities of the arm, shoulder, and hand scores pre- and postoperatively improved from 43 to 0.7, respectively. The mean postoperative grip strength was measured of the injured hand (40 kg) and un-injured hand (41 kg). CONCLUSIONS: Retrograde headless intramedullary screw fixation of fifth metacarpal neck and shaft fractures has overall favorable early outcomes and offers the benefit of stable fixation, early motion without cast immobilization, and the ability for early return to work. This technique is a viable surgical option for these fractures and may be considered in the appropriate patient population.